Ð˜Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ðµ Ð¸Ð½Ñ‚ÐµÐ½ÑÐ¸Ð²Ð½Ð¾ÑÑ‚Ð¸ Ñ„Ð»ÑƒÐ¾Ñ€ÐµÑÑ†ÐµÐ½Ñ†Ð¸Ð¸ ÐºÐ»ÐµÑ‚Ð¾Ðº Ð¼ÐµÑ€Ð¸ÑÑ‚ÐµÐ¼Ð½Ð¾Ð¹ Ñ‚ÐºÐ°Ð½Ð¸ Ð²Ð¸Ð½Ð¾Ð³Ñ€Ð°Ð´Ð° Ð¿Ð¾Ð´ Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸ÐµÐ¼ Ñ€ÑÐ´Ð° ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² - Stribul, T. F.; Lysak, Yu. S.; Kompaniets, A. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
The effect of some substances with cryoprotective properties on grape meristem fluorescence and viability was studied. Treated with cryoprotectants meristems were irradiated with laser to excite photoelectron emission and the fluorescence spectra were obtained in 1, 3, 5, 20 and 120 min. It has been established that the effect of cryoprotective agents (CPAs) manifested in the change of fluorescence intensity within the range of the studied wave lengths.